Seismic and aseismic slip during the 2006 Copiapó swarm in North-Central Chile. (March 2023) - Ojeda, Javier; Morales-Yáñez, Catalina; Ducret, Gabriel; Ruiz, Sergio; Grandin, Raphael; Doin, Marie-Pierre; Vigny, Christophe; Nocquet, Jean-Mathieu
Abstract: Earthquake swarms commonly occur along the Chilean subduction zone, witnessing fast seismic and slow aseismic slip behavior at the plate interface. However, the largest seismic swarms observed in Chile, particularly in the Copiapó-Atacama region, remain poorly documented, and the underlying processes have yet to be understood. Here, we perform seismological and geodetic analyses to investigate the 2006 Copiapó swarm, which developed in April and May 2006. The swarm began on April 19, with a magnitude Ml 5.3 earthquake. During the nine following days, we observe a migration of seismicity along the plate interface, the occurrence of doublets events, and a potential slow slip event in the GPS time series at site Copiapó. Then, on April 30, a first earthquake with Mw 6.6 occurred at 15 km depth at the plate contact. It likely triggered a second earthquake of magnitude Mw 6.5, which occurred 144 min later, 10 km northwest of the first earthquake. Using InSAR, we determined the slip distribution associated with these two earthquakes and detailed the postseismic slip they triggered in the next days and weeks. This "postseismic" phase appears to be predominantly aseismic, while the moment released during the "coseismic" phase is comparable to other seismic crises that occurred in Atacama. Although we did not find a larger seismic and aseismic ratio than in other swarms in South America, we suggest a similar mechanism of slow deformation as a driver of seismicity during seismic swarms. Finally, we propose that the slow and fast behavior of the 2006 Copiapó swarm is a consequence of the subduction of the Copiapó Ridge seamounts, which affects both the plate interface and the overriding plate by inducing complex interactions between seismic and aseismic processes. Highlights: We study a three-week-long seismic swarm involving two M > 6 earthquakes. Seismological analysis reveals a complex migration pattern of seismicity. GPS data suggest that slow aseismic slip occurs at the beginning of the sequence. InSAR data highlights the afterslip down-dip of the two largest earthquakes. The diversity of slow and fast slip likely results from the subduction of Copiapó Ridge seamounts.